New Pentecostalism in the Wake of the Economic Crisis in Cameroon (Nordic Journal of African Studies, 2002)
In recent decades there has been an upsurge of Pentecostal groups in Cameroon. This new wave of Pentecostal groups is coming in with the 'prosperity doctrine' as an economic message at a time when Cameroon is experiencing a serious economic crisis. This is contrary to the ascetic position taken by the mainline Pentecostal churches before the economic crisis started. This article reveals that the mainline Pentecostal churches have, with the crisis, shifted their attention to the 'prosperity doctrine'. It argues that the economic crisis has contributed to the flourishing of these churches and that the shift in the economic message of the mainline groups is a survival strategy.